Improving ethnocultural data to inform public health responses to communicable diseases in Australia - Quinn, Emma; Massey, Peter; Rosewell, Alexander; Smith, Mitchell; Durrheim, David (Western Pacific Surveillance and Response, 2014)
The ethnicity of migrants is associated with a differential risk of infectious diseases, including measles, hepatitis B and tuberculosis, in Australia and other western countries. In Australia, there is no national strategy to support standardised collection of priority ethnocultural communicable disease data. We explore the utility of existing surveillance data to describe ethnocultural groups and the potential for including new variables to improve disease prevention and control in New South Wales (NSW), Australia for high priority diseases. Currently there is a lack of ethnocultural data to help identify and describe the risk of communicable diseases for second and third generation Australians. The collection of data on “ethnicity/ancestry” in NSW on an ad-hoc basis has recently improved disease control activity for second and third generation Australians and should be considered for routine inclusion in notifiable disease surveillance in NSW within a national framework.